Review: hCGs: Different sources of production, different glycoforms and functions - Fournier, T.; Guibourdenche, J.; Evain-Brion, D. (Placenta (Eastbourne), 2015)
Human chorionic gonadotropin (hCG) is the first hormonal message from the placenta to the mother. It is detectable in maternal blood two days after implantation and behaves like an agonist of LH stimulating progesterone secretion by the corpus luteum. hCG has also a role in quiescence of the myometrium and local immune tolerance. Specific to humans, hCG is a complex glycoprotein composed of two glycosylated subunits. The α-subunit is identical to the pituitary gonadotropin hormones (LH, FSH, TSH), contains two N-glycosylation sites, and is encoded by a single gene (CGA). By contrast the β-subunits are distinct in each of the hormones and confer receptor and biological specificity. The hCG β-subunit contains two sites of N-glycosylation and four sites of O-glycosylation and is encoded by a cluster of genes (CGB). In this review, we will stress the importance of hCG glycosylation state, which varies with the stage of pregnancy, its source of production and in the pathology. It is well established that hCG is mainly secreted by the syncytiotrophoblast into maternal blood where it peaks around 8–10 weeks of gestation (WG). The invasive extravillous trophoblast also secretes hCG, and in particular like choriocarcinoma cells, hyperglycosylated forms of hCG (hCG-H). In maternal blood hCG-H is high during early first trimester. In addition to its endocrine role, hCG has autocrine and paracrine roles. It promotes formation of the syncytiotrophoblast and angiogenesis through LHCG receptor. In contrast, hCG-H stimulates trophoblast invasion and angiogenesis by interacting with the TGFβ receptor 2. hCG is largely used in antenatal screening and hCG-H represents a serum marker of early trophoblast invasion. Other abnormally glycosylated hCG are described in aneuploidies. In conclusion, hCG is the major pregnancy glycoprotein hormone, whose maternal concentration and glycan structure change all along pregnancy. Depending on its source of production, glycoforms of hCG display different biological activities and functions that are essential for pregnancy outcome.